Relationship between project liability period and project quality / Nor Akmal Tarmizi - Tarmizi, Nor Akmal (Faculty of Civil Engineering, 2006)
The topic will discuss about the relationship between defects liability period and project quality after completion. The objectives of this topic are to study the sufficiency and the defect liability period in relations to the project quality. Developers want to avoid a long defect liability periods in order to avoid the further liability on the project defects. As an example, in Malaysia, normally people will buy house before it is completed while in another country people will normally buy a completed house. Some developers will construct a project without really taking into consideration the project quality after completion. Many construction companies in Malaysia are not certified to ISO quality standard. Therefore, many projects are completed without fully complying with the required specifications and standards. This is not a good phenomenon in the nation construction industry. The result of this project show there is a relationship between project liability period and project quality. When defects liability period increase, the total defect will decrease. That is mean more total defect will give lower project quality. Defects liability period must amendment to suitable period to get better project quality.